2005
DOI: 10.1016/j.febslet.2005.07.023
|View full text |Cite
|
Sign up to set email alerts
|

NosX function connects to nitrous oxide (N2O) reduction by affecting the CuZ center of NosZ and its activity in vivo

Abstract: The effect of loss of the 34-kDa periplasmic NosX protein on the properties of N 2 O reductase was investigated with an N 2 O-respiration negative, double mutant of the paralogous genes nosX and nirX of Paracoccus denitrificans. In spite of absence of whole-cell N 2 O-reducing activity, the purified reductase was catalytically active, which attributes NosX a physiological role in sustaining the reaction cycle. N 2 O reductase exhibited the spectroscopic features of Cu A and the redox-inert, paramagnetic state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In the recent work of Zumft et al [36], it is reported that in Paracoccus denitrificans, the in vitro N 2 O reducing capacity is higher in cells from which N 2 OR is isolated with the CuZ centre mainly as CuZ [2Cu 2þ : 2Cu þ ] then when it is mainly in the CuZ* [1Cu 2þ : 3Cu þ ] state. However, after isolation, both enzyme forms have similarly low specific activities (3.6 U mg…”
Section: Results and Discussion (A) Microaerobic Culture Of Marinobacmentioning
confidence: 99%
“…In the recent work of Zumft et al [36], it is reported that in Paracoccus denitrificans, the in vitro N 2 O reducing capacity is higher in cells from which N 2 OR is isolated with the CuZ centre mainly as CuZ [2Cu 2þ : 2Cu þ ] then when it is mainly in the CuZ* [1Cu 2þ : 3Cu þ ] state. However, after isolation, both enzyme forms have similarly low specific activities (3.6 U mg…”
Section: Results and Discussion (A) Microaerobic Culture Of Marinobacmentioning
confidence: 99%
“…1278,1290,1315 In the absence of the NosR and NosX proteins accessory proteins, N 2 OR purified under anaerobic conditions has identical characteristics to aerobically purified protein. 1305,1306 These differences take on new significance with the recent publication of a crystal structure of anaerobically prepared PsN 2 OR which shows a different structure for the Cu Z site than that observed for aerobically prepared protein (see Section 5.2.3). 1296 Early biochemical studies and the recent X-ray structure agree that aerobically and anaerobically purified N 2 OR have identical molecular weights and protein structure.…”
Section: 0 Copper Sites In Bacterial Denitrificationmentioning
confidence: 99%
“…1305 A similar phenotype is obtained in the absence of the NosX gene product for organisms that contain NosX, which codes for another periplasmic flavoprotein. 1306 This suggests that NosR and NosX are not involved in Cu Z biogenesis but play a role altering the state of the Cu Z site during turnover and sustaining the catalytic activity of N 2 OR. If NosR and NosX are in fact required to sustain N 2 O reduction in vivo, further study of the process of Cu Z biogenesis and maintenance will be necessary to define the full catalytic mechanism of N 2 OR.…”
Section: 0 Copper Sites In Bacterial Denitrificationmentioning
confidence: 99%
“…The other difference was found in the pH dependence of the catalytic activity, which is higher at basic pH values for methylviologen, whereas for cytochrome c-552 it is higher at more acidic values. The different reactivity is proposed to be correlated to a different type of interaction of methylviologen toward the enzyme, in particular owing to a direct reduction of the CuZ center, overpassing the internal electron flow between the CuA and CuZ centers of N 2 OR [88].…”
Section: Catalytic Properties Of Cuz and Reaction Intermediatesmentioning
confidence: 99%